The classic fairy tales : texts, criticism - Tatar, Maria (A Norton critical edition, 2017)
This is a superb anthology of fairy tales and criticism that is perfect for classroom use. It provides an excellent selection of primary and secondary texts, organized to permit a wide variety of approaches to teaching the fairy tale. Tatar's introductions to each section are balanced, up-to-date, and provocative." --Donald Haase, Wayne State University "Wonderful, comprehensive book!" Hope L. Russell, SUNY Buffalo